PRODUCING AFLIBERCEPT LOADED POLY (LACTIC-co-GLYCOLIC ACID) [PLGA] NANOPARTICLES AS A NEW OCULAR DRUG DELIVERY SYSTEM AND ITS CHALLENGES - Karagoz, Isil Kutluturk; Allahverdiyev, Adil; Demircioglu, Atifcan; Abamor, Emrah Sefik; Dinparvar, Sahar; Bagirova, Melehat (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
The aim of the present study is to develop a new drug delivery system with the aid of nanomedicine for aflibercept molecule and to evaluate optimization, characterization, in vitro drug release profile and toxicity on human retinal pigment epithelial (ARPE-19) and human retinal endothelial cell (HREC) lines. Poly lactic-co-glycolic acid (PLGA) aflibercept nanoparticles were prepared using the doubleemulsion diffusion and solvent evaporation technique. The Dynamic Light Scattering (DLS), UV-vis absorption (UV), Scanning Electron Microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy techniques were carried out to characterize the nanoparticles. Cytotoxic effects of blank PLGA and Aflibercept-loaded PLGA nanoparticles on ARPE19 and HREC cells were evaluated using the 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide salt (MTT) assay. Aflibercept-loaded PLGA nanoparticles with a round shape and smooth surface were produced and verified with SEM images. The average particle size, polydispersity index (PdI) and zeta potential value were 262 +/- 6.6 mV; 0.12 +/- 0.016 mV and +6.27 +/- 4 mV respectively. The release of aflibercept was extended up to 48 hours with the 85.2 +/- 1.08 % encapsulation and 10.4 +/- 4.5 % loading efficiency. The formation of encapsulation was verified with FT-IR analysis and in vitro toxic effects on both cell lines have also been observed at various doses ranging from 0.1 mu M to 0.5 mu M. The development of nanoparticle-based drug delivery systems is challenging and time consuming, and requires optimization of several factors before their use in clinical practice. 48 hours in vitro relase may not adequate to claim improvement over Aflibercept delivery in vivo. Further studies are needed.
Keywords: Anti -VEGF; Drug Delivery; Nanoparticle; Retina; INTRAVITREAL BEVACIZUMAB AVASTIN; VEGF-TRAP; MACULAR DEGENERATION; INTRAOCULAR PHARMACOKINETICS; RANIBIZUMAB; INJECTION; TOXICITY; SINGLE; EYE; NEOVASCULARIZATION; Environmental Sciences & Ecology